Relevansi Pendidikan Anak dalam Islam Perspektif Abdullah Nashih ‘Ulwan dan Kurikulum Merdeka di Sekolah Dasar - Zulfa, Athena; Zuhriyah, Amifatuz (Institut Agama Islam Daruttaqwa Gresik, 2024)
Abdullah Nashih ‘Ulwan presents views on educating children in Islam based on the teachings of Prophet Muhammad (PBUH) in the book